IMPLEMENTASI SKALA HWISE PADA PENGUKURAN TINGKAT KERAWANAN AIR RUMAH TANGGA DI DESA OBOH KOTA SUBULUSSALAM - Soleha, Siti; Urfan, Faiz (Jurnal Samudra Geografi, 2025)
Household water insecurity is defined as the inability of individuals to access adequate, reliable, and safe water. This study aims to measure and analyze the level of household water insecurity around the Lae Souraya River in Desa Oboh, Rundeng District, Subulussalam City. This research employed a quantitative approach using a survey method. The primary instrument used was the Household Water Insecurity Experiences (HWISE) Scale, which was administered to 80 respondents. The data were analyzed using descriptive statistics to describe the prevalence and scale of water insecurity. The findings indicate a high level of water insecurity, with 76% of households classified as water-insecure. This high prevalence suggests that the majority of households frequently experience worries and challenges related to water accessibility, quantity, and quality for domestic purposes such as drinking, cooking, and hygiene. This research can serve as an empirical basis for policymaking aimed at improving public health and welfare in Desa Oboh.